Depletion of PSMD14 suppresses bladder cancer proliferation by regulating GPX4 - Changxin Jia; Xin Zhang; Tingting Qu; Xiuyun Wu; Yu Li; Yang Zhao; Lijiang Sun; Qing Wang (PeerJ, 2023)
Objective The aim of this study was to investigate the role of deubiquitinase (DUB) 26S proteasome non-ATPase regulatory subunit 14 (PSMD14) in patients with bladder cancer. Methods From 2016 to 2018, 181 patients diagnosed with primary bladder cancer at the Affiliated Hospital of Qingdao University were recruited. The expression of PSMD14 in bladder cancer tissues was tested by immunochemistry. The association between PSMD14 expression and clinical and pathological data and outcomes of bladder cancer patients was determined. Overexpression and knockdown cells were constructed to evaluate the effects of PSMD14 on proliferation of bladder cancer cells. Results Our results showed that PSMD14 was significantly overexpressed in bladder cancer tissues compared to adjacent non-tumor tissues (76.24% vs 23.76%, P = 0.02). The expression of PSMD14 was significantly higher in patients with larger tumor diameters (85.14% vs 70.09%, P = 0.019) and patients with a family history of cancer (92.16% vs 70.00%, P = 0.002). Patients with high expression of PSMD14 had poor disease-free survival (DFS) (HR = 2.89, 95% CI [1.247–6.711], P = 0.013). Gain and loss of function experiments demonstrated that PSMD14 deficiency inhibited bladder cancer cell proliferation. Additionally, depletion of PSMD14 suppressed bladder cancer cell growth via down-regulation of GPX4, and the promotion of PSMD14-induced cell growth was observably reversed by the GPX4 inhibitor RSL3. Conclusion We determined that PSMD14 is highly expressed in bladder cancer tissues, and that PSMD14 expression correlated with poor disease-free survival. Depletion of PSMD14 could inhibit the proliferation of bladder cancer cells through the downregulation of GPX4. Therefore, PSMD14 may be an effective target for the treatment of bladder cancer.